Potret Keluarga dalam Novel Anak Sejuta Bintang Karya Akmal Nasery Basral - Hanifah, Hanifah; Asri, Yasnur (Indonesian and Regional Language and Literature Department, Universitas Negeri Padang, 2023)
The purposes of the study were to describe and analyze the factors behind a parent's attitude toward the first child and to describe and analyze the level of volunteerism between the relationship between the parent and the first child in the novel with the social realities of the family in society. This is qualitative research with descriptive methods. The source of the data of this research is Akmal Nasery Basral’s novel, Anak Juta Bintang. This research data is the units of events in the novel. The result of the study shows that the factors behind the attitude of parents towards the first child are factors of birth order and culture. The realitytion, based on the level of excitement between the relationship of parents and the first child in the novel Children of a Million Stars with the social reality of the family in the community proved quite high. This conclusion directs the assessment recommendation that the novel Anak Juta Bintang is a novel that successfully reveals the social reality of society in family relationships.